Corrosion and tribocorrosion behaviour of Ti6Al4V produced by selective laser melting and hot pressing in comparison with the commercial alloy - Toptan, Fatih (2019)
The corrosion and tribocorrosion behaviour of SLM-produced Ti6Al4V alloy was studied in comparison with its HP and commercial counterparts in 9 g/L NaClsolution at body temperature. Results showed that SLM processing route influenced the electrochemical response of the SLM-produced alloy by leading to a relatively lower quality for the passive film due to decreased beta phase and the formation of alpha' phase. However, after tribocorrosion, neither the total volume loss nor the volume loss under the influence of mechanical wear and wear accelerated corrosion showed any statistically significant difference between the processing routes.